The economic dimensions of transnational organised crime in Southern and Western Africa - Tolulope Lembola Ojolo; Shanta Balgobind Singh (International Review of Social Sciences Research)
This article explores the economic dimensions of transnational organised crime (TOC) in Africa, focusing on the Southern and Western regions. TOC in Africa, while driven by traditional motives such as power and financial gain, has evolved into a sophisticated form of criminal entrepreneurship. This evolution is closely linked to globalization, technological advancements, and socio-political instability across the continent. We examine how criminal networks exploit economic and regulatory gaps to integrate illicit activities into the formal economy, thereby blurring the distinction between legal and illegal enterprises. The article critically discusses the vulnerabilities that facilitate TOC in Africa, such as governance-related challenges, corruption, and socio-economic inequalities. A special emphasis is placed on industries such as eco-tourism and real estate, which have become key channels for money laundering and other illegal activities on the continent, as well as the impact of TOC on the continent's social and economic development. The enterprise model of organised crime and the entrepreneurial theory of crime are used as theoretical frameworks to analyse the operational dynamics of these criminal networks. By providing a comprehensive analysis of TOC as a variation of entrepreneurship, particularly within the shadow economy, this article fills a critical gap in the literature. There is an urgent need for a robust legal framework and international cooperation to combat the growing influence of TOC in Africa, which poses a significant threat to the continent's economic stability and development.